2002
DOI: 10.1074/jbc.m200764200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Transcriptional Intermediary Factor 2 Nuclear Receptor Box Peptides with the Coactivator Binding Site of Estrogen Receptor α

Abstract: The activation function 2/ligand-dependent interaction between nuclear receptors and their coregulators is mediated by a short consensus motif, the so-called nuclear receptor (NR) box. Nuclear receptors exhibit distinct preferences for such motifs depending both on the bound ligand and on the NR box sequence. To better understand the structural basis of motif recognition, we characterized the interaction between estrogen receptor ␣ and the NR box regions of the p160 coactivator TIF2. We have determined the cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
160
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(171 citation statements)
references
References 38 publications
9
160
2
Order By: Relevance
“…In fact, the crystal structures of PGC-1␣ NR3 displayed the right orientation of the LXXYL motif when it binds to ERR␣ (40,41). A similar finding was made with an LXXYL motif from another NR coactivator when the crystal structure of SRC2 NR3 in complex with ER␣ displayed the LXXYL motif in right orientation (71). Fur-FIGURE 6.…”
Section: Discussionsupporting
confidence: 62%
“…In fact, the crystal structures of PGC-1␣ NR3 displayed the right orientation of the LXXYL motif when it binds to ERR␣ (40,41). A similar finding was made with an LXXYL motif from another NR coactivator when the crystal structure of SRC2 NR3 in complex with ER␣ displayed the LXXYL motif in right orientation (71). Fur-FIGURE 6.…”
Section: Discussionsupporting
confidence: 62%
“…This view is supported by studies of short peptides containing a single NR box reporting preferential binding of specific NR boxes to NRs (14)(15)(16). However, such studies neglect the influence of protein conformation on binding (17). We demonstrated that eliminating NR box III by truncating SRC1NID changes the binding properties in a nontrivial way.…”
Section: Discussionmentioning
confidence: 70%
“…By a computer-based protein modeling approach , we recently identified a putative regulatory intramolecular interaction between a motif included in the P295-T311 sequence (aa 301-311) and the helix H4 which is located within a region known to recruit co-regulators (H3-H5) (Warnmark et al, 2002;Kong et al, 2005). Hence, the estrogen-like activity of ERa17p might stem from its ability to interfere with this regulatory mechanism.…”
Section: Discussionmentioning
confidence: 99%